One-dimensional man : studies in the ideology of advanced industrial society - Marcuse, Herbert (Routledge, 2002)
One of the most important texts of modern times, Herbert Marcuse's analysis and image of a one-dimensional man in a one-dimensional society has shaped many young radical's way of seeing and experiencing life.